PENGARUH ETOS KERJA DAN DISIPLIN KERJA TERHADAP EFEKTIFITAS KERJA KARYAWAN PADA PT SURYA PRIMA SEJAHTERA PALEMBANG - Firdaus Sianipar; Amrillah Azrin (JURNAL KOMPETITIF, 2020)
This study aims to determine the effect of work ethic and work discipline on the work of employees of PT. Surya Prima Sejahtera Palembang, The population in this study were all employees and a research sample of 20 employees (saturated sample). Multiple regression analysis aims to calculate the magnitude of the effect of a change in events. In this study, multiple regression analysis acts as a statistical technique used to test whether there is an effect of work ethic and work discipline on the work effectiveness of employees at PT. Surya Prima Sejahtera. Simultaneous F significant test results. From the results, it shows that the independent variables together do not have a significant effect on the dependent variable, this is because the significant value f 0.135> 0.05. This proves that Work Ethic (X1) and Work Discipline (X2) together have no influence on employee performance. The result of the t test (partial), it is known that the value of t count is 2.375, this means that the value of t is greater than the value of t table 2.365 (based on t table). As for the significance value of work ethic (X1) 0.049 <0.05, which means that Ho is rejected and Ha is accepted. This means that there is a significant influence between the work ethic variable (X1) and employee performance (Y).  Keywords:work ethic, work discipline, performance